2009
DOI: 10.1016/j.bmcl.2008.10.133
|View full text |Cite
|
Sign up to set email alerts
|

Biologically relevant chemical properties of peroxymonophosphate (O3POOH)

Abstract: It has been suggested that peroxymonophosphate could serve as an endogenous hydrogen peroxide-derived regulator of cellular protein tyrosine phosphatase activity under physiological or pathophysiological conditions. To facilitate further consideration of the potential role of peroxymonophosphate in biological systems we present studies related to the preparation, characterization, stability, and flourometric detection of this agent..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…That reaction is typical for hypohalous ions and nucleophilic peroxy oxidants (Fig. 7) [53,55,56]. A few years ago, we demonstrated that boronates react rapidly with hypochlorite and peroxynitrite anions [51,53] (Fig.…”
Section: Introductionmentioning
confidence: 75%
“…That reaction is typical for hypohalous ions and nucleophilic peroxy oxidants (Fig. 7) [53,55,56]. A few years ago, we demonstrated that boronates react rapidly with hypochlorite and peroxynitrite anions [51,53] (Fig.…”
Section: Introductionmentioning
confidence: 75%
“…LaButii et al reported peroxymonophosphate ( 2− O 3 POOH) as an exceptional inactivator of PTP1B with K I = 6.6 × 10 −7 M and k inact = 0.043 s −1.90 As a result, peroxymonophosphate ( k inact / K I = 65,553 M −1 s −1 ) is approximately 7,000 times more potent than hydrogen peroxide, an endogenous regulator of PTP1B. 91 Like hydrogen peroxide, peroxymonophosphate is also an active-site directed and thiol reversible inactivator of PTP1B. In a recent study, Meng & Zhang showed that hydroxyl radical could also be a viable oxidizing agent for the PTP active site under physiological conditions.…”
Section: Covalent Ptp Inhibitorsmentioning
confidence: 99%
“…Because of the crosstalk between PTPs and kinases in regulation of diverse biological processes, studies have also emerged in understanding the nature of endogenous oxidants responsible for the inactivation of this class of enzymes. For instance, relatively stable H2O2 inactivates PTP1B at ~1,000-fold slower rates than peroxymonophosphate (PMP), when the reactions were performed under similar conditions [99,100]. There is the question of whether PMP is actually formed in vivo as potential metabolizing enzymes such as catalase were found ineffective towards this reactive species.…”
Section: Redox Regulation Of Signalingmentioning
confidence: 99%